(untitled) (Eureka Journal of Humanities and Social Research, 2025)
This study investigates how social media narratives shape public opinion and collective behavior in contemporary societies. Through a mixed-methods approach involving content analysis and digital ethnography, the research explores how algorithms, emotional contagion, and echo chambers influence individual and group decision-making. Findings reveal that social media platforms serve not only as information sources but also as identity-building arenas that can both unify and polarize communities.